Toxicity of combined targeted therapy and concurrent radiotherapy in metastatic melanoma patients: a single-center retrospective analysis. Issue 6 (December 2020) - Ziegler, Johanna S.; Kroeze, Stephanie; Hilbers, Marie-Luise; Imhof, Laurence; Guckenberger, Matthias; Levesque, Mitchell P.; Dummer, Reinhard; Cheng, Phil; Mangana, Joanna
Abstract : The Eastern Cooperative Oncology Group consensus guidelines from 2016 recommend interruption of targeted therapy with BRAF- and MEK-inhibitors during radiotherapy with data being based mostly on BRAF monotherapy. The aim of this study is to provide data on the safety of concurrent radiotherapy and combination targeted therapy with BRAF- and MEK-inhibitors. A total of 32 patients with 51 sessions of radiotherapy from one center receiving concurrent radiotherapy and BRAF- and MEK- inhibitors were included. Radiotherapy-associated toxicities were retrospectively collected. Incidence was compared between three groups: (A) targeted therapy during radiotherapy with and, (B) without interruption, and (C) radiotherapy before the start of targeted therapy. Survival and local disease control were examined. Targeted therapy was interrupted during radiotherapy in 16, not interrupted in 14, and only started after radiotherapy in 21 sessions. Stereotactic radiotherapy was applied in 28 sessions, conventionally fractionated radiotherapy in 23. The brain was the most common site of irradiation ( n  = 36). Radiotherapy-associated toxicities occurred in 41.2% ( n  = 21) of sessions and did not differ significantly among the groups. Overall survival was 11.7 months and progression-free survival was 8.4 months. No increase in radiotherapy-associated toxicity was seen where combination targeted therapy was not interrupted during radiotherapy. Prospective clinical trials are warranted to support our findings. Abstract : Supplemental Digital Content is available in the text.